If f(−3)=−4 and f′(−3)=6, find the equation of the tangent line to f at x=−3. a) y=−4x+6 b) y=6x+14 c) y=−4x−6 d) y=6x−4 e) y=6x−22

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

If f(−3)=−4 and f′(−3)=6, find the equation of the tangent line to f at x=−3. a) y=−4x+6 b) y=6x+14 c) y=−4x−6 d) y=6x−4 e) y=6x−22

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

I know that the slope is f'(x) so 6, I'm just not sure what to do the rest of the way.
@satellite73 this is my last question of the night, could you help?
use the points slope form

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

y-y1=m(x-x1)
i know m but how to i get y1 and x1?
\[m=6,(x_1,x_2)=(-3,-4)\]
you don't get them, you are told them
Oh! that makes sense! thank you.

Not the answer you are looking for?

Search for more explanations.

Ask your own question